EFEKTIFITAS KOMUNIKASI PEMASARAN PADA USAHA MIKRO, KECIL DAN MENENGAH BIDANG KULINER DI SURABAYA - Veronika Rahmawati; Andy Pratama (Catholic University Musi Charitas, 2019)
From year to year, the number of micro and small and medium enterprises in Indonesia is increasing, and this is accompanied by increasing awareness of entrepreneurship in Indonesia. Starting from young people to retirees, they began to pursue the work of becoming entrepreneurs of MSMEs. An increase in the number of small and medium-sized businesses in Indonesia, contributes positively to economic conditions in Indonesia, for those around the MSMEs location, through MSMEs the community is able to move the economy of the Indonesian economy. The increasing number of MSMEs certainly allows for more, each of the appropriate facilities for progress that has been made effectively by MSMEs. This study uses a quantitative approach to determine the influence of Marketing Communication Objectives and Communication Channels on Marketing Communication Effectiveness. The population in this study was to use GENERAL samples in the culinary field in Surabaya as many as 136 MSMEs respondents in Surabaya were taken by purposive sampling which was processed using multiple regression techniques with SPSS applications. This study aims to determine the positive relationship between Marketing Communication and Marketing Communication on the Effectiveness and Physical Effectiveness of Communication Channels on the Effectiveness of Marketing Communication.